Cover Image. (7th June 2018) - Pinto, S.I.S.; Campos, J.B.L.M.; Azevedo, E.; Castro, C.F.; Sousa, L.C.
Abstract : The cover image, by S.I.S. Pinto et al., is based on the Research Article Numerical study on the hemodynamics of patient‐specific carotid bifurcation using a new mesh approach, https://doi.org/10.1002/cnm.2972 .